2020
DOI: 10.1080/07391102.2020.1850360
|View full text |Cite
|
Sign up to set email alerts
|

Computational gene expression profiling in the exploration of biomarkers, non-coding functional RNAs and drug perturbagens for COVID-19

Abstract: The coronavirus disease, caused by the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), is a global health crisis that is being endured with an increased alarm of transmission each day. Though the pandemic has activated innumerable research attention to decipher an antidote, fundamental understanding of the molecular mechanisms is necessary to halt the disease progression. The study focused on comparison of the COVID-19 infected lung tissue gene expression datasets-GSE155241 and GSE150316 with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 84 publications
(88 reference statements)
0
8
0
Order By: Relevance
“…reported in other SARS-CoV-2 related papers (Aishwarya et al, 2020;Vastrad et al, 2020). Ankryin B, which aligns to SP597-606, has been reported to be transcribed in lungs of COVID-19 patients, where it is not usually expressed (Aishwarya et al, 2020), and ZNF354C, aligning to NP361-390, is a transcription factor which interacts with genes that are differentially expressed in SARS-CoV-2 infected patients (Vastrad et al, 2020).…”
Section: Self-proteins Share Disease Associations Which Relate To Symptoms Reported In Covid-19 Patientsmentioning
confidence: 79%
“…reported in other SARS-CoV-2 related papers (Aishwarya et al, 2020;Vastrad et al, 2020). Ankryin B, which aligns to SP597-606, has been reported to be transcribed in lungs of COVID-19 patients, where it is not usually expressed (Aishwarya et al, 2020), and ZNF354C, aligning to NP361-390, is a transcription factor which interacts with genes that are differentially expressed in SARS-CoV-2 infected patients (Vastrad et al, 2020).…”
Section: Self-proteins Share Disease Associations Which Relate To Symptoms Reported In Covid-19 Patientsmentioning
confidence: 79%
“…The authors revealed that proscillaridin A could effectively inhibit the replication of SARS-CoV-2 3CL pro in Vero cells at an IC 50 of 2.04 μM ( Liu et al, 2020a ). Furthermore, proscillaridin A exhibited a low binding energy (−80.06 Kcal/mol) and well interactions (six interactions) with SARS-CoV-2 M pro ; in addition, this study provided additional evidence relating to the potential molecular mechanisms of action ( Aishwarya et al, 2020 ).…”
Section: Promising Active Ingredients Of Chinese Herbal Medicine Thatmentioning
confidence: 75%
“…Among these 10 drugs, the cytotoxic drugs chromium (III) chloride and irinotecan hydrochloride should not be considered as candidates. Antimycin A ( 52 ), proscillaridin ( 53 , 54 ), troglitazone ( 55 , 56 ), thapsigargin ( 57 , 58 ), genistein ( 59 , 60 ), and testosterone ( 61 ) were considered as potential drugs for COVID-19 in previous studies. Acetovanillone and hyperforin have not been studied for the treatment of COVID-19.…”
Section: Discussionmentioning
confidence: 99%